Experimental Study on Automatic Control for Collision Avoidance of Ships - Paroka, Daeng; Kamil, Muhammad Fahmi; Muhammad, Andi Haris (UI Scholars Hub, 2017)
Automatic control system is widely applied to control the ship direction or heading angle in accordance with the decided trajectory. Several methods for improving performance of control system have been developed such as Proportional-Integral-Derivative (PID) control and fuzzy logic based control. Within the last decade, application of automatic control system is not only for ship navigation but also for avoiding collision risk of ships in seaways. This paper discusses the application of automatic control system for avoiding ship collision by free running experiment. Fuzzy logic based control was developed using Mamdani Centroid method to estimate the necessary rudder angle in order to change the ship heading angle. Collision scenario was designed using four fixed obstacles with a certain distance which will be avoided by ship model. The results of free running experiment showed that the automatic control system can minimize the risk against collision or at least provide initial warning that may be faced by the ship. with minimum distance of 3.50 of length between perpendicular. To improve performance of control, external disturbance such as wind and wave should be considered in the design of automatic control system.